2008
DOI: 10.1158/1541-7786.mcr-08-0032
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of c-Jun NH2-Terminal Kinase and p38 Mitogen-Activated Protein Kinase in the Cellular Response to Ionizing Radiation in Human Cervical Cancer Cells

Abstract: Exposure of cells to ionizing radiation induces activation of multiple signaling pathways that play critical roles in determining cell fate. However, the molecular basis for cell death or survival signaling in response to radiation is unclear at present. Here, we show opposing roles of the c-jun NH 2 -terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK) pathways in the mitochondrial cell death in response to ionizing radiation in human cervical cancer cells. Ionizing radiation triggered Bax an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
(49 reference statements)
5
21
0
Order By: Relevance
“…In this study, the activation of MAPK by stress-inducing agents promoted an increased level of phosphorylated H2AX, a marker of DNA damage caused by double-strand breaks [54], as demonstrated previously in other cellular systems [19][20][21][22]55,56]. actions as sensors of DNA strand break sites [57].…”
Section: Accepted Manuscriptsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, the activation of MAPK by stress-inducing agents promoted an increased level of phosphorylated H2AX, a marker of DNA damage caused by double-strand breaks [54], as demonstrated previously in other cellular systems [19][20][21][22]55,56]. actions as sensors of DNA strand break sites [57].…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…In situations of cellular stress, such as serum starvation, specific isoforms of MAPK are closely regulated [21]. In addition, following the exposure of cervical cancer cells to IR, such as gamma radiation, apoptosis is triggered, as mediated by JNK, and p38 MAPK is activated, with opposite effects on regulation of the Bax, Bak and Bcl-2 proteins [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our assertion that p38 plays a role in cell survival is supported by a number of recent reports linking this signaling pathway to increased levels of BCL2 and BCL-x l in response to DNA damage and stress (12,23). Furthermore, the chemical inhibition of p38 has been strongly associated with increased chemosensitivity in cancer cells (16,30).…”
Section: Discussionsupporting
confidence: 66%
“…In colorectal cancer cells, a novel cell type-specific role of p38α MAPK is found to control and mediate autophagy (Kim et al 2008a). Either autophagy or apoptosis has been found to be regulated by JNK-mediated Bcl-2 phosphorylation (Kim et al 2008b). Wei et al reported that JNK1-mediated Bcl-2 phosphorylation interferes with its binding to the proautophagy BH3 domain-containing protein Beclin 1, and had a dual role in autophagy and apoptosis regulation (Wei et al 2008).…”
Section: Discussionmentioning
confidence: 99%